Theory of Mind - Della Raymena Jovanka; Denny Setiawan (Bandar Lampung University (UBL), 2013)
This paper aimed to describe preschool age children’s Theory of Mind, as a part of their cognitive development. Some factors that affect the children’s Theory of Mind are parental talking, social economic background, parents’ education, etc.The research participants are 82 preschool age children in South Jakarta, Indonesia. The method used in this paper was quasi experiment, adaptated from Sobel, Li, and Corriveau’s method. The statistical data were examined by one way ANOVA. These data suggest that the judgment of preschool age children’s learning comprehension is based on one’s behavior, not according to one’s desire, attention, and intention to learn. This research can be an additional reference for early childhood education curriculum, especially in cognitive area and teaching strategy